Penerapan Manajemen Perubahan sebagai Upaya Meningkatkan Konsep Diri dalam Komunikasi Internasional Mahasiswa Universitas Islam Negeri Sumatera Utara - Melati Devyana; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
The ability to communicate effectively is highly demanded in the students of the leading nation's leaders & intellectuals. But some students that some of them have difficulty in communicating interpersonal, such as talking in class, talking to lecturers, and speaking in a campus organization environment. They have anxiety and fears while interacting with others. As a result, they more with ideas, feelings and thoughts, avoiding interaction or meet others. Therefore, the author aims to provide solutions for students with the application of change management as an effort to improve self-concept in student interpersonal communication. The data set is done by using the literature study, the theoretical study, references and other scientific literature related to culture, value and norms that develop in the social situation are studied. From the reference books obtained how to solve the problem based on theories and the formulas that have been tested and recognized in general.